Theoretical Analysis of Carbon Nano Tubes - K. , Lakshmi Tanuja; Balachander, Bhuvaneswari (International Journal of Psychosocial Rehabilitation, 2020)
In nanotechnology, carbon nanotubes are the most important material. The carbon nanotubes are used in nanotechnology, membranes, polymers, and nanomedicine, and carbon nanotubes are used in cell culture, etc. In this article, the types of carbon nanotubes, applications, and properties are discussed. Carbon nanotubes are an allotropic form of carbon, and they come under the fullerene family.